PENGARUH KINERJA LINGKUNGAN, KINERJA KEUANGAN, FIRM SIZE, DAN FIRM VALUE TERHADAP ENVIRONMENTAL INFORMATION DISCLOSURE - Nora Akhsa; Darsono Darsono (Diponegoro Journal of Accounting, 2021)
The aim of this research is to examine the effects of environmental performance, financial performance, firm size, and firm value on environmental information disclosure in manufacturing and mining firms in Indonesia. Measurement of Environmental Information Disclosure based on Indonesian Environmental Reporting Index (IER). There are 35 items to detect Environmental Information Disclosure through the annual report. Population in this research were a manufacturing and mining company that listed on the Indonesia Stock Exchange in 2016-2018 consistently. Purposive sampling was used as a sampling method and obtained 105 companies as a samples. The analysis tool used is multiple linear regression. The result show that environmental performance, firm size, and firm value has a positive effect on environmental information disclosure. Whereas, financial performance which consists of profitability and leverage does not affect on environmental information disclosure.